Finite element method (FEM) approach towards composite material / Ahmad Shehan Nordin - Nordin, Ahmad Shehan (2002)
The objective of this project is to examine the behavior of composite under uniformly distributed loading on the top surface in the z-direction. The analysis of these elements consists of stress, strain and the displacement. There were two methods that have been used to examine these elements, which were theory and finite element method. LUSAS software has been used to associate with the finite element method. In finite element method it self, we consider two type of model to be analyzed. Which were 2-dimensional and 3-dimensional analysis. First type we obtain the result from quarter model and second type from full (real) model. Unfortunately the FEM results tabulated a significant percentage of errors. Therefore, more read-up was accumulated to signify possible reasoning for the percentage errors that kept occurring. (% Errors is the difference of value of the FEM displacement and the theoretical values the thesis by J.N. Reddy & A.K. Pandey, " A First Ply Failure Analysis of Composite Laminates")